The future of insurance regulation and supervision : a global perspective - Liedtke, Patrick M.; Monkiewicz, Jan. (Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2011)
Written by leading academics, researchers and insurance industry experts, this book offers a diversified perspective on how the regulatory and supervisory framework for the insurance sector will develop over the coming years. It is supported by The Geneva Association, the world-leading insurance think-tank of the private industry.
"Written by leading academics, researchers and insurance industry experts, this book offers a diversified perspective on how the regulatory and supervisory framework for the insurance sector will develop over the coming years. It is supported by The Geneva Association, the world-leading insurance think-tank of the private industry"-- Provided by publisher.
Includes bibliographical references and index.
oif 17/09/14
Loan
Keywords: Insurance